THE USING SILENT WAY EFFECTIVE IN TEACHING PLURAL NOUNS TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI 1 RANTEPAO - Carli Baka (Teaching English as a Foreign Language Overseas Journal, 2016)
The objective of the research is to find out the effectivess of the silent way in teachingplural nouns to the eight grade students of SMP Negeri 1 Rantepao This research held atSMP NEGERI 1 RANTEPAO’’.North Toraja regency,.The population consists of the number of subjects was surveyed in the research andit is hoped the results can be generalized. The population of this research is theeighth grade students of SMP NEGERI 1 RANTEPAO’ that consists of six classes.The numbers of students is 193.The samples of this research were a part of the grade students of SMP NEGERI 1RANTEPAO’. The number of sample is 30 students. The writer use cluster samplingto get the data. The instrument of this study is written testBased on the findings and discussions of the previous chapter, the writer concludethat the implementation of silent way in teaching plural nouns to the eighth gradestudents of SMP NEGERI 1 RANTEPAO’ have a good score effective. This factis prove by the students have good score and classified as good score and theresult of post-test mean score which is higher than the mean score of pre-test.